The Implementation of Genetic Algorithm in The Vehicle KIR Test Scheduling System - Suprihadi Suprihadi; Rama Aufadha Risqullah (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
Based on the results of observations and data collection, the vehicle parking test services at the Salatiga City Transportation Agency have not implemented a structured scheduling system in managing their service schedules. This has resulted in an accumulation of the number of vehicles that exceed the service capacity on a working day. Therefore, a scheduling system is needed to assist the agency in arranging the due time schedule for the KIR test of a vehicle, and helping the vehicle owner community to find out the due time for the next KIR test. The scheduling method used is a genetic algorithm that is applied to a web-based application. The application is built using the PHP language and MySql database. With this website-based scheduling system application, it has made it easier for service officers to manage the KIR test service schedule, especially if there is a change in the number of vehicles.